Shenfu Formula reduces cardiomyocyte apoptosis in heart failure rats by regulating microRNAs. (5th December 2018) - Yan, Xu; Wu, Hongjin; Ren, Jianxun; Liu, Yuna; Wang, Shengqi; Yang, Jiyuan; Qin, Shuyan; Wu, Delin
Abstract: Ethnopharmacological relevance: Shenfu decoction consists of the water extract from the dried root or rootstalk of Panax ginseng C. A. Mey (Asian ginseng) and the lateral root of Aconitum carmichaeli Debx (Fuzi, Heishunpian in Chinese). Shenfu Formula has been used as a folk Chinese medicine for thousands of years. Recent studies have shown that Shenfu injection can enhance cardiac function and regulate arrhythmia. Aim of the study: Shenfu Formula plays an important role in the treatment of heart failure. However, its microRNA-mediated mechanisms are still not fully understood. Thus, we established a heart failure model in rats to investigate the microRNA mechanism of Shenfu Formula in cardiac function and apoptosis. Materials and methods: The heart failure animal model was established via left-anterior descending coronary artery ligation in rats. Seven days after surgery, Shenfu Formula was given to the heart failure rats, which were selected by echocardiography with an LVEF< 45%. After Shenfu Formula was given intragastrically for 30 days, blood samples were drawn, the heart was excised after echocardiography, and echocardiographic parameters and apoptosis-related proteins were further examined. Fas/Fas-L and Bcl-2/Bax proteins were analyzed by Western blot, and microRNAs were evaluated using Affymetrix GeneChip miRNA arrays. Results: Shenfu Formula increased the left ventricular ejection fraction, improved the hemodynamic index of heart failure rats, and decreased serum brain natriuretic peptide (BNP) levels. Shenfu Formula also decreased the positive rate of myocardial cells as detected by the TUNEL method and significantly suppressed caspase 3 expression. Moreover, we found that Shenfu Formula can regulate the initiative factors Fas/Fas-L in the intrinsic pathway and Bcl-2/Bax in the extrinsic apoptosis pathway to suppress apoptosis in heart failure rats. Finally, Shenfu Formula potentially alters the balance of microRNAs involved in activating and inhibiting apoptosis, ultimately suppressing apoptosis; this leads to changes in the gene expression profiles of microRNAs targets. Conclusion: Shenfu Granule can effectively improve cardiac function in heart failure rats, and the anti-apoptosis effects of Shenfu Formula are potential mechanisms for inhibiting heart failure. Graphical abstract: